The bees of Singapore (Hymenoptera: Apoidea: Anthophila): first comprehensive country checklist and conservation assessment for a Southeast Asian bee fauna - Ascher, John S. (2023)
Reports of global bee declines have raised an urgent call for assessments of the conservation status of these key pollinators. The first published checklist and conservation status assessment for the bee fauna of a Southeast Asian country is presented here. A total of 133 species, comprising 106 named species and an additional 27 distinct morphospecies, have been recorded in the Singapore checklist. Conservation statuses were assessed for all species using a decision table adapted from the IUCN Red List criteria, accounting for documented site occurrences, habitat associations, and year of last record. Of key conservation importance are six Nationally Extinct species, six Critically Endangered species, two Endangered species, and 12 Vulnerable species. A relatively high proportion of stingless bee species (five of fourteen) in tribe Meliponini are either Nationally Extinct or Critically Endangered, suggesting that these highly eusocial bees are of particular conservation concern. Whereas 16 bee species have been recorded only from historical records (from 1976 or before), 117 species persist (recorded 2009–2021), with 79 (68%) of these in urban or semi-urban areas such as city parks and rooftop gardens. The 44 (33.1%) Data Deficient species are poorly known locally and continued monitoring and inventorying of bees is needed to inform management of Singapore’s pollinators. Several bee species have only recently been confirmed for Singapore. Some synonymies and taxonomic comments presented first in a recently published book on Singaporean bees are discussed. Eupetersia (Nesoeupetersia) malayensis (Blüthgen, 1927) is treated as a provisional senior synonym of Eupetersia (Nesoeupetersia) singaporensis Pauly, 2012, and E. (N.) sabahensis Pauly, 2012. We recognise Trigona (Tetragonula) pagdeniformis Sakagami, 1987, as a junior synonym of the Trigona laeviceps Smith, 1857 (non auct.), with current combination Tetragonula (Tetragonula) laeviceps (Smith, 1857), and recognise Tetragonula (Tetragonula) valdezi (Cockerell, 1918) as a valid species.